Roles of Helicobacter pylori in the Epithelial-Mesenchymal Transition of Gastric Cancer - Ruan, Shuai; Huang, Wenjie; Wen, Fang; Lu, Xiaona; Gu, Su Ping; Chen, Xiao Xue; Liu, Miao; Shu, Peng (Archives of Clinical and Biomedical Research, 2020)
Gastric cancer (GC) is one of the most frequent malignant tumors in humans, with over 50% of patients after treatment suffering from recurrence and peritoneal metastasis. Helicobacter pylori (H. pylori) infection is critical to the development of GC. The phenomenon of epithelial-mesenchymal transition (EMT) in GC is linked with development of the invasive phenotype, which is very likely regulated by H. pylori through altering signaling pathways in the gastric cells. In this review, we conclude the current studies on how H. pylori affects the EMT of GC, thus contributing to its initiation and metastasis.